General trends between solute segregation tendency and grain boundary character in aluminum - An ab inito study. (1st October 2018) - Mahjoub, Reza; Laws, Kevin J.; Stanford, Nikki; Ferry, Michael
Abstract: Quantum mechanical calculations have been performed to establish general trends in propensity for the segregation of solutes across the periodic table at or in the neighborhood of an extended set of commonly observed special grain boundaries in face centered cubic aluminium. To this end, Al has been considered as the matrix and elements from 3d and 4d transition metals as well as those from group II, III and IV have been selected as solute atoms. For transition metal solutes, we find a concave-up parabolic-like dependency of segregation energy as a function of atomic number that is argued to be caused by the competition between chemical bonding and atomic size effects. The analysis is corroborated quantitatively by the computation of crystal orbital Hamiltonian population for solute-Al and Al-Al pairs as well as the Voronoi polyhedral surrounding solutes at a sample GB. The parabolic-like (concave-down trend) dependency of the cohesiveness of grain boundaries is explained by an equivalent trend in the bonding strength of Al-Al pairs at the segregated GBs. We extend this investigation to examine the stability of the solid solution polycrystalline state by comparing the calculated segregation energy against the combined energetic cost of grain boundary and intermetallic precipitate formation. The results may serve as a design tool for tailoring polycrystalline alloys with desired properties. Graphical abstract: Image 1